MANAJEMEN PROGRAM ACARA RONA MELAYU DI TELEVISI REPUBLIK INDONESIA (TVRI) RIAU-KEPRI DALAM MELESTARIKAN KEBUDAYAAN MELAYU - Putra, Try Rama; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The event program hue malay is program talkshow that aims to provide the knowledge and information and features related to the Malay culture. This program was created based on the reality of the people of Riau who lack knowledge about the Malay culture. Serving this program can affect the view and build the public mindset about the Malay culture. The purpose of this study was to determine how management program wither on television hue Republic of Indonesia (TVRI) Riau-kepri in preserving Malay culture.This study uses a qualitative approach is the management deskriptif.Objects research program wither on television hue republic Indonesia ( TVRI) Riau-kepri in preserving Malay culture produced by TVRI Riau. Subjects consisted of five informants that the head of the program TVRI Riau-kepriThe result of the findings of this research that describes how the application of planning, organizing, actuating, and controlling (POAC)in the program management event hue wither in an effort to produce product quality event. Rona Malay implement the first 4 stages planning,organizing,actuating, controllingKeyword : Malay Rona Events Manament TVRI, Malay Culture in sustainin